The Effect of Service Quality, Product Quality, and Pricing on the Level of Customer Satisfaction at PT. IT Matsuoka Winner Industry - Wulandari, Romadona Ayu; Yuniawan, Ahyar (JURNAL BISNIS STRATEGI, 2023)
This study aims to understand the level of customer satisfaction with service quality, product quality, and price at PT. Ti Matsuoka Industry Winner. This study uses variables of service quality, product quality and price as independent variables and consumer satisfaction as the dependent variable. The population in this study used all consumer data of PT. Ti Matsuoka Industry Winner. With a sample of 118 individuals using the purposive sampling method. The data analysis method used in this study is multiple linear regression technique. The results of the analysis show that the variables of service quality, product quality and price have a positive and significant effect on consumer satisfaction at PT. Ti Matsuoka Winner Industry. And in this study price has a dominant influence on consumer satisfaction.